Percepção dos professores sobre o uso da tecnologia no ensino e aprendizagem da Geração Z - Guerin, Cíntia Soares (2020)
The present study had as main objective to understand the perception of teachers regarding the influence of Information and Communication Technologies in the teaching and learning of Generation Z students. This is a qualitative research with a semi-structured data collection instrument applied to teachers of a public school in the city of Foz do Iguaçu / PR. The selected target audience is represented by a sample of 19 teachers who responded to the interview between the months of April and August 2019. For the analysis and interpretation of the data, the Collective Subject Discourse technique was used, which is a possibility of analysis preliminary report of the subjects to select the central ideas of the participants. The results demonstrated through the teachers' report showed an enormous influence of Information and Communication Technologies in the school environment. This scenario was visible from the interviews that show the concern of educators with the teaching and learning of their students and the institution's initiative to keep up to date on the subject at all times, always concerned with acquiring technological materials to assist in the acquisition of knowledge. Above all, training courses focused on the use of information and communication technologies in the teaching and learning of Generation Z are reduced or do not include the real need of teachers, thus, the mechanisms for attracting students during the moments of teaching and learning in the classroom need to be reviewed. Therefore, it is concluded that more than providing information and communication technologies to schools or stimulating their use, circumstances must be provided for teaching and learning to take place in a solid and effective way. It is necessary to invest in teacher training, so that educators can use technological equipment and resources for the benefit of education and for pedagogical purposes. In this logic, a transformation of political thought is indispensable for achieving quality education. Having education as a priority, as disseminated by all government officials, consists in expanding investment in an uninterrupted and long-term manner, not only attributing equipment to institutions, but also presenting conditions of use to improve the pedagogical purpose. In addition, the need to trace new paths in the teaching and learning process, compatible with the knowledge of the 21st century.